2017
DOI: 10.5455/medarh.2017.71.351-355
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ethics for Providing Telemedicine Services and Information Technology

Abstract: Introduction:Advanced technology has increased the use of telemedicine and Information Technology (IT) in treating or rehabilitating diseases. An increased use of technology increases the importance of the ethical issues involved. The need for keeping patients’ information confidential and secure, controlling a number of therapists’ inefficiency as well as raising the quality of healthcare services necessitates adequate heed to ethical issues in telemedicine provision.Aim:The goal of this review is gathering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 40 publications
1
60
0
13
Order By: Relevance
“…E-health can help patients with 'white coat syndrome'. Email communication and interactive video medical visits that could be used to change the typical communication process and potentially reduce anxiety [21]. However, doctors globally are concerned about the lack of protection of the privacy of patient information in this way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-health can help patients with 'white coat syndrome'. Email communication and interactive video medical visits that could be used to change the typical communication process and potentially reduce anxiety [21]. However, doctors globally are concerned about the lack of protection of the privacy of patient information in this way.…”
Section: Discussionmentioning
confidence: 99%
“…However, doctors globally are concerned about the lack of protection of the privacy of patient information in this way. Capturing patient records by unauthorized persons may jeopardize the principle of the protection of private information of patients and may be able to misuse [21]. A nation-wide study showed e-health as a means to combat communicable diseases like tuberculosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…The Information Technology (IT) has deeply affected various occupations and social applications. Such kind of technology has occasioned the quality improvement and decreased the administrative costs of different occupations, hence in the health care section [1,2]. Utilizing the IT in the health care system, especially in the hospitals imbeds several potentials in improving of service quality and personnel efficiency, and decreasing the organizational costs.…”
Section: Introductionmentioning
confidence: 99%
“…With the recognition that society is beginning to accept telemedicine, certain ethical issues have been noted. [21] Ethical issues in telemedicine were first identified in the early 1980s. In 2006, the WHO assigned the American Society for Bioethics and Humanities the task of identifying ethical issues in telemedicine.…”
Section: Balancing Ethics and Innovationmentioning
confidence: 99%
“…Their goal was to improve the quality of healthcare through the identification, analysis and resolution of certain ethical questions, and to promote practices consistent with ethical norms and standards, by advising institutional efforts in telemedicine policy development. [21][22][23] As the law often lags behind technological development, an enhancement and realignment of normative frameworks may be required to address certain ethical gaps. [3] The question is how, and to what extent, we identify the boundaries between viable solutions and futility that may be blurred by technology?…”
Section: Balancing Ethics and Innovationmentioning
confidence: 99%